Hamstring strain injuries: are we heading in the right direction?. Issue 2 (15th June 2011) - Mendiguchia, Jurdan; Alentorn-Geli, Eduard; Brughelli, Matt
Abstract : Acute hamstring injuries are the most prevalent muscle injuries reported in sport. Despite a thorough and concentrated effort to prevent and rehabilitate hamstring injuries, injury occurrence and re-injury rates have not improved over the last three decades. This failure is most likely due to the following: (1) a lack of studies with high level of evidence into the identification and prevention of hamstring injuries and (2) a reductionist approach of the current literature. The objectives of this article are to review and critique the current literature regarding isolated risk factors, and introduce a new concept for a more comprehensive scientific understanding of how multiple risk factors contribute to hamstring strain injury. The authors hope that this new conceptual model can serve as a foundation for future evidence-based research and aid in the development of new prevention methods to decrease the high incidence of this type of injury.